Planning Strategies for Increasing the Occupancy Rate of Green Open Space Based on Urban Geographic Data in Macau: An Investigation of Ultra-High-Density Cities - Jitai Li; Fan Lin; Hongcan Cui; Yile Chen; Shuai Yang (Buildings)
Urban green space can effectively optimize the urban landscape and environment and provide residents with space for daily leisure and recreational activities. In order to realize the green development of Macau, this paper takes the Macau Special Administrative Region (SAR) as an example, uses the green open space occupancy rate (GOSOR) to measure the level of green open space in Macau, and researches the planning positioning of Macau City’s green development, the layout mode of urban public open space, and the integration and optimization of the space in Largo of high-density neighborhoods, so as to explore the planning paradigm of Macau’s green development. In addition, the research data show that the per capita green area of Macau Peninsula is on the low side and extremely unbalanced, and there is a disconnection between some of the large-scale green patches on Macau Outlying Island; therefore, this paper proposes that the planning layout mode of “green veins connecting green patches” is suitable for Macau Peninsula and that the planning layout mode of “greenways embedded in jade” is suitable for Macau Outlying Island. On the other hand, in order to improve the problem of poor living conditions in the high-density city of Macau, the study proposes to make use of the unutilized Macau Largo space and carry out the optimization and transformation of the Largo space from “gray to green”, so as to release a large amount of green open space and enhance the GOSOR value of the high-density street area of Macau Peninsula.